2017
DOI: 10.1037/hea0000512
|View full text |Cite
|
Sign up to set email alerts
|

Buffer or amplifier? Longitudinal effects of social support for functional autonomy/dependence on older adults’ chronic pain experiences.

Abstract: Objective: This longitudinal study aimed to investigate: (1) the moderating role of formal social support for functional autonomy versus dependence on the relationship between pain intensity and pain-related disability among older adults with chronic pain, and (2) the mediating role of pain-related self-efficacy and pain-related fear in this moderation. Methods:One hundred and seventy older adults (M age =78.0; SD=8.7) with chronic musculoskeletal pain participated in a 3-month prospective study, with three me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 79 publications
1
18
0
1
Order By: Relevance
“…However, the relationship between changes in kinesiophobia at 6 months and changes in disability at 6 months was not reported. On the other hand, Matos et al 74 reported that kinesiophobia at baseline did not predict changes in disability at 3 months. No covariates were reported.…”
Section: Resultsmentioning
confidence: 98%
“…However, the relationship between changes in kinesiophobia at 6 months and changes in disability at 6 months was not reported. On the other hand, Matos et al 74 reported that kinesiophobia at baseline did not predict changes in disability at 3 months. No covariates were reported.…”
Section: Resultsmentioning
confidence: 98%
“…However, enforced close-proximity living could also bring challenges to autonomy and independence. Although social support can help buffer against pain, 14,15,18,56 an increase in solicitous behaviours in such close proximity might unintentionally contribute to the chronicity of pain. 34,43,72 For example, in households where a child is in pain, increased social proximity could lead to increased exposure to protective parental behaviours and reductions in child autonomy and activity.…”
Section: Risk Of Increased Social Proximitymentioning
confidence: 99%
“…According to the socalled social buffer hypothesis (Cohen and McKay 1984), negative effects of stressors on health and well-being are reduced or even eliminated by receiving social support from social ties. This hypothesized moderation effect has been empirically found in multiple studies across various contexts (Barth et al 2010;Bowen et al 2014;Cohen and Wills 1985;Earnshaw et al 2015;Holtfreter et al 2017;Holt-Lunstad et al 2010;Kondrat et al 2017;Matos et al 2017;Thoits 1995Thoits , 2011Uchino 2004Uchino , 2009). Social support could be influential in the relation between health problems and employment by providing different types of social support.…”
Section: The Protective Effect Of Close Social Tiesmentioning
confidence: 76%